FamData: Database for Family Business Companies in Germany Covering Company Key Figures and Survey Data - Johanna Garnitz; Annette von Maltzan; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2023)
FamData is a database covering family businesses and non-family businesses across various size classes and branches containing structural and financial information. The ifo Institute assembled a business panel with executives from almost 4,000 companies. In addition to the "hard" business data like turnover and number of employees, the database also includes "soft" survey data. The latter one covers information from regular – at least yearly - surveys treating topics like investment behavior, skilled labor shortage or reaction of firms during the Corona pandemic situation and the rise in energy prices observed in 2022.
Keywords: C80; C81; C83; D22; 330; family businesses; micro data; surveys